2010
DOI: 10.1007/s00167-010-1133-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting injury severity among recreational skiers and snowboarders: an epidemiology study

Abstract: Different results have been reported for skiing and snowboarding injuries worldwide. Few studies consider the injury severity score (ISS) for the evaluation of differences among injured skiers-snowboarders. The aim of this study is to identify possible risk factors that affect the severity of skiing and snowboarding injuries in three winter seasons (2002-2005) in South Tyrol. For every injured skier or snowboarder referred to our emergency department in three consecutive seasons, the following data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
5
25
0
Order By: Relevance
“…Since the 1970s, their incidence has dropped by half while upper extremity fractures and knees sprains became the most common injury types [29,30]. Our results are consistent with previous studies evidencing an increase in the volume of orthopaedic procedures performed during winter around ski resorts [5,6,8,9,10,11,31,32]. The observed peak in emergency admissions for open surgery was primarily associated with tourist populations.…”
Section: Main Findings and Comparison With Other Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…Since the 1970s, their incidence has dropped by half while upper extremity fractures and knees sprains became the most common injury types [29,30]. Our results are consistent with previous studies evidencing an increase in the volume of orthopaedic procedures performed during winter around ski resorts [5,6,8,9,10,11,31,32]. The observed peak in emergency admissions for open surgery was primarily associated with tourist populations.…”
Section: Main Findings and Comparison With Other Studiessupporting
confidence: 89%
“…We assumed that an increased tourist influx coupled with high-risk injury cases [10] could saturate the emergency departments and disturb hospitals' internal organization by exceeding bed capacity and available staff resources [13]. Previous studies suggest that hospital crowding can lead to higher risks of mortality [14,15,16], readmission [14,16], and adverse events [14,15,16] for patients with longer stays [14].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of injury mechanism, those at the beginner level are likely to injure themselves during an isolated fall 16 29 30. However, when snowboarding injuries are stratified by skill-level, these types of injuries decrease and high-impact injuries associated with attempted expert tricks become more traumatic and more prevalent across all injury locations 9 16 29 52 53…”
Section: Methodsmentioning
confidence: 99%
“…Continuing with the epidemiology review, Girardi et al [9] studied factors affecting injury severity using the Injury Severity Score (ISS). They found that being a man and being older than 60 years were risk factors for an increased ISS, while the ISS was lower in beginner skiers and during a snowfall.…”
Section: Amateur Skiersmentioning
confidence: 99%